2015
DOI: 10.1089/wound.2014.0596
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of a Novel Topical Negative Pressure Device in Promoting Healing in Chronic Wounds

Abstract: Aim: This observational study evaluated the use of a novel, ultraportable, mechanically powered topical negative pressure device in promoting healing in chronic wounds, including venous and mixed etiology leg ulcers and neuropathic foot ulcers. Materials and Methods: Evaluable patients (n = 37) received treatment with the SNaP Ò Wound Care System for up to 6 weeks. The primary objective was percentage change in wound size, with secondary objectives of clinical assessment of wound parameters, ease of use, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…A substantial 15 patients experienced wound infection and underwent treatment suspension until the infection resolved. However, 46% of patients reported an improvement in the overall quality of life, and indicated that the SNaP system was user‐friendly and less burdensome than conventional NPWT …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A substantial 15 patients experienced wound infection and underwent treatment suspension until the infection resolved. However, 46% of patients reported an improvement in the overall quality of life, and indicated that the SNaP system was user‐friendly and less burdensome than conventional NPWT …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the overall quality of the current evidence remains poor, comprising of sporadic case series, retrospective studies, and only two RCTs with inconsistent conclusions. Whilst no firm conclusion can be made regarding its superiority over current NPWT systems in terms of wound‐healing outcomes, there are clear benefits from the shorter device application time, improved patient satisfaction, and quality of life …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficult-to-debride wounds [166]. Necrotic pressure ulcer; recurrent venous leg ulceration [167] Provides a moist environment.…”
Section: Commercial Medical-grade Honeymentioning
confidence: 99%
“…Ainda, seis (17,1%) estudos eram de coorte (29)(30)(31)(32)(33)(34) , três (8,6%) observacionais longitudinais (35)(36)(37) , e um (2,9%) caso-controle (38) . Os outros 11 (31,4%) eram estudos com abordagem descritiva (5,7,(39)(40)(41)(42)(43)(44)(45)(46)(47) Dentre os estudos que compuseram esta revisão, 26 (74,3%) utilizaram diferentes instrumentos validados para a avaliação do processo de cicatrização de lesões de pele, sendo que em três (8,6%) estudos, foram utilizados mais de um instrumento. Os demais estudos (25,7%) utilizaram a observação e a mensuração de variáveis clínicas para a avaliação das lesões e de características complementares das lesões.…”
Section: Para a Seleção Dos Estudos Foram Adotadas As Recomendações D...unclassified